Incidence of microsporidia in cancer patients - Lono, A.R.; Kumar, S.; Chye, T.T. (2008)
Introduction Microsporidia are considered opportunistic pathogens as evidenced by the significant detection in immunocompromised HIV/AIDS population. Cancer patients receiving chemotherapy are considered to be immunosuppressed. Materials and Methods Stool samples were collected from 311 cancer patients in the Klang Valley. Each sample underwent waterâether concentration and staining with modified trichrome stain. Results and Discussion Sixty-eight samples were positive by oil immersion examination. Polymerase chain reaction amplification with specific primers on those samples amplified Encephalitozoon intestinalis from two of the samples and Encephalitozoon hellem from one sample.